A study on drying models and internal stresses of the rice kernel during infrared drying. Issue 6 (26th April 2017) - Wu, Jiazheng; Zhang, Hengwei; Li, Fan
ABSTRACT: Due to the limited penetration of infrared, it is very difficult to develop an infrared drying model of rice kernels. In this study, two kinds of simplified drying models, which assumed the penetration depth is infinity and zero, were developed to investigate the effects of penetration on drying characteristics of thin layer infrared drying. The results show each model can predict temperature and moisture contents (MC) accurately. The maximum temperature difference of rice kernels in both models was always less than 1.5°C, so it is reasonable to exclude the influence of thermal stresses due to nonuniform temperature. This study also developed the internal stresses model with the mechanical properties from literatures. Mechanical properties were with the changes of temperature and MC. These models were solved with COMSOL Multiphysics and there are two stress concentration areas. One is near the surface of the endosperm, another close to the center. Comparison between the von Mises stress distribution and the moisture gradient was made after the simulation. The maximum MC in the endosperm appeared at its surface, which reached 190 1/m at 110 s, and the maximum stress appeared at the same place, which, a little later, reached 7 MPa at 160 s. Moisture gradient at the center was zero due to the existence of symmetry, while there was a significant stress, which reached 3.2 MPa during drying.